Boosting the water dissociation kinetics via charge redistribution of ruthenium decorated on S, N-codoped carbon. Issue 31 (2nd August 2021) - Li, Tingya; Zhang, Xueyan; Chen, Yilan; Zhong, Lixiang; Li, Shuzhou; Zhang, Peixin; Zhao, Chenyang
Abstract : A simple yet robust route to the synthesis of Ru decorated S, N co-doped carbon (denoted Ru-SNC) is reported. The Ru-SNC-2 exhibits a superior catalytic performance due to the boosted water dissociation kinetics with an η @10 of only 14 mV. Abstract : A simple copolymer template strategy for the synthesis of sulfur and nitrogen co-doped carbon decorated by Ru (Ru-SNC) is reported for the efficient alkaline HER. The Ru-SNC catalyst, with a Ru content of 2.59 wt%, only needs an extremely low overpotential of 14 mV to deliver the benchmark 10 mA cm −2 in 1 M KOH. Additionally, yielding a hydrogen generation rate that is 15.6 times higher than that of commercial Pt/C at an overpotential of 25 mV places Ru-SNC among the topmost active alkaline HER electrocatalysts. The high activity of Ru-SNC is uncovered by X-ray absorption fine structure spectra and theoretical calculations, revealing a modified surface charge distribution of Ru through Ru-N/S bonds that results in an optimized Ru–H* interaction and a greatly reduced energy barrier for water dissociation. This simple strategy provides new insights into the development of highly efficient alkaline HER catalysts and can be readily extended to the formation of other highly active metal-based electrocatalysts.